The search for new amphiphiles: synthesis of a modular, high-throughput library - Feast, George C.; Lepitre, Thomas; Mulet, Xavier; Conn, Charlotte E.; Hutt, Oliver E.; Savage, G. Paul; Drummond, Calum J. (Beilstein Journal of Organic Chemistry, 2014)
Amphiphilic compounds are used in a variety of applications due to their lyotropic liquid-crystalline phase formation, however only a limited number of compounds, in a potentially limitless field, are currently in use. A library of organic amphiphilic compounds was synthesised consisting of glucose, galactose, lactose, xylose and mannose head groups and double and triple-chain hydrophobic tails. A modular, high-throughput approach was developed, whereby head and tail components were conjugated using the copper-catalysed azide–alkyne cycloaddition (CuAAC) reaction. The tails were synthesised from two core alkyne-tethered intermediates, which were subsequently functionalised with hydrocarbon chains varying in length and degree of unsaturation and branching, while the five sugar head groups were selected with ranging substitution patterns and anomeric linkages. A library of 80 amphiphiles was subsequently produced, using a 24-vial array, with the majority formed in very good to excellent yields. A preliminary assessment of the liquid-crystalline phase behaviour is also presented.
Keywords: amphiphiles; carbohydrates; click chemistry; high throughput; library synthesis